Establishment of probabilistic model for Salmonella Enteritidis growth and inactivation under acid and osmotic pressure - Yujiao Shi; Hong Liu; Baozhang Luo; Yangtai Liu; Siyuan Yue; Qing Liu; Qingli Dong (Food Science and Human Wellness)
The growth and survival characteristic of Salmonella Enteritidis under acidic and osmotic conditions were studied. Meanwhile, a probabilistic model based on the theory of cell division and mortality was established to predict the growth or inactivation of S. Enteritidis. The experimental results demonstrated that the growth curves of planktonic and detached cells showed a significant difference (p < 0.05) under four conditions, including pH5.0 + 0.0%NaCl, pH7.0 + 4.0%NaCl, pH6.0 + 4.0%NaCl, and pH5.0 + 4.0%NaCl. And the established primary and secondary models could describe the growth of S. enteritis well by estimating four mathematics evaluation indexes, including determination coefficient (R2), root mean square error (RMSE), accuracy factor (Af) and bias factor (Bf). Moreover, sequential treatment of 15% NaCl stress followed by pH 4.5 stress was the best condition to inactivate S. Enteritidis in 10 h at 25 °C. The probabilistic model with Logistical or Weibullian form could also predict the inactivation of S. Enteritidis well, thus realize the unification of predictive model to some extent or generalization of inactivation model. Furthermore, the primary 4-parameter probabilistic model or generalized inactivation model had slightly higher applicability and reliability to describe the growth or inactivation of S. Enteritidis than Baranyi model or exponential inactivation model within the experimental range in this study. Keywords: Acid, Osmotic pressure, Salmonella Enteritidis, Probabilistic model, Unification, Generalization